Adherence to dabigatran and the influence of dabigatran-induced gastrointestinal discomfort in the real-world practice. (15th January 2021) - Hwang, Jongmin; Lee, So-Ryoung; Park, Hyoung-Seob; Lee, Young Soo; Ahn, Jin Hee; Choi, Jong-Il; Shin, Dong Gu; Kim, Dae-Kyeong; Park, Jong Sung; Hwang, Ki Won; Cha, Tae-Joon; Choi, Eue-Keun; et al.
Abstract: Background: Dabigatran-induced gastrointestinal discomfort (DGID) is an important factor influencing the adherence to dabigatran. We investigated the incidence and risk factors of DGID and its impact on the adherence and persistence to dabigatran. Methods: We prospectively enrolled the patients prescribed with dabigatran in 10 tertiary hospitals of the South Korea. The adherence was assessed using the percentage of the prescribed doses of the medication presumably taken by the patient (PDT by pill count). We evaluated the relationship between DGID and the baseline GI symptoms or the previous GI disease history using a questionnaire. Results: A total of 474 patients (mean age 67.8 ± 9.3 years, male 68.6%, and mean CHA2 DS2 -VASc score 2.2 ± 1.2) were enrolled. The adherence assessed by the PDT was 93.5 ± 5.5% at 1-month and 96.4 ± 8.4% at 6-months among the persistent patients. During the 6-month follow-up, 82 (18.1%) patients discontinued dabigatran, and the most common reason for dabigatran discontinuation was DGID (49, 59.8%). Sixty-eight (14.3%) patients experienced DGID, and there was no difference in the clinical factors between those with or without DGID. Among the patients who experienced DGID, 42 discontinued dabigatran (61.8%). In a multivariate analysis, DGID was the only predictor of dabigatran discontinuation and a low adherence. Conclusion: Overall adherence of dabigatran was excellent, but those with DGID showed low adherence and persistence. Furthermore, it was challenging to predict DGID by clinical parameters. Therefore, it is recommended to follow the patients closely to check for DGID when prescribing dabigatran. Highlights: Six-month persistence of dabigatran was 82%. The incidence of dabigatran induced gastrointestinal discomfort (DGID) was 14.3%. DGID was the most common reason for dabigatran discontinuation (59.8%). More than half of the patients (61.8%) who experienced DGID discontinued dabigatran. It was difficult to predict DGID by clinical parameters.